The Novel LncRNA AK035396 Drives Cardiomyocyte Apoptosis Through Mterf1 in Myocardial Ischemia/Reperfusion Injury - Xu, Zhaoyan; Mo, Yuanxi; Li, Xinyi; Hong, Wanzi; Shao, Sisi; Liu, Yaoxin; Shu, Fen; Jiang, Lei; Tan, Ning (Frontiers in Cell and Developmental Biology, 2021)
Background:Myocardial ischaemia/reperfusion (I/R) injury is still a major challenge in clinical treatment. The role of long non-coding RNA (lncRNA) in the regulation of  myocardial I/R injury still needs to be elucidated. Methods:The primary isolated neonatal mousse cardiomyocytes and adult mice were used to construct a myocardial ischemia-reperfusion model. qRT-PCR is used to verify gene expression in myocardial tissue and myocardial cells. The effect of AK035396 in primary cardiomyocytes and mouse myocardium was confirmed by TUNEL staining and in vitro flow cytometry experiments. RNA pulldown and Western blot were used to identify AK035396 interacting proteins. The expression of apoptosis-related proteins was identified by qRT-PCR and Western blot. Results: In vivo and in vitro MIRI models, AK035396 was up-regulated after myocardial infarction. Functional studies have shown that knockdown of AK035396 reduces the apoptosis of primary cardiomyocytes and mouse myocardial tissue. AK035396 directly interacts with Mterf1 and inhibits the level of Mterf1. Further experiments have shown that inhibiting Mterf1 will promote the expression of mitochondrial genes COXII and CYTb and cause cell apoptosis. Conclusion:AK035396 plays an important role in myocardial ischaemia-reperfusion injury by regulating the Mterf1-COXII/CYTb pathway.